FACTORS ASSOCIATED WITH THE SUBJECTIVE FEELING OF FATIGUE THREE MONTHS AFTER COVID-19 - Mihajlović, Dejan; Virijević, Mirjana; Radovanović, Ana (Srpski medicinski časopis Lekarske komore, 2022)
Introduction: The subjective feeling of fatigue is one of the most common post-COVID-19 manifestations. It is characterized by intolerance to physical and cognitive effort that the individual previously tolerated well, accompanied by weakness and other symptoms.Aim: The aim of this study was to examine the frequency of the subjective feeling of fatigue, three months after recovery from the infection, amongst patients who had been infected with COVID-19, as well as to analyze correlated factors.Methods: This cross-sectional study included 110 patients who had previously contracted COVID-19, and who came for a regular follow-up examination at the Health Center Kosovska Mitrovica, 3 months after recovery from acute infection. A specially designed questionnaire was used, which consisted of the segment with sociodemographic data, the segment with the data on the patient’s health status and the course of their COVID-19 infection, as well as the segment of the questionnaire related to self-assessment of the patient’s health status after the COVID-19 infection.Results: In our sample, out of 110 respondents, as many as 52 felt fatigue. Factors that were statistically significantly associated with the subjective feeling of fatigue, three months after treatment, were the age of the subject and the presence of chronic disease (p < 0.05). The presence of fever and pneumonia during infection were statistically significantly associated with the presence of the subjective feeling of fatigue, three months after treatment (p < 0.05). Hospitalized patients and those who were hospitalized for a longer period of time were also more likely to feel fatigue three months after recovering from the infection (p < 0.05).Conclusion: The subjective feeling of fatigue, as one of post-COVID manifestations, as well as the consequent inability of the patient to resume work-related and personal tasks and responsibilities, can be a serious individual and public health problem, which is why it is necessary to appropriately recognize and treat it.
Keywords: fatigue; COVID-19; post-COVID-19; self-assessment